Synthesis and characterization of a bimetallic boratabenzene cobalt complex - Hascall, T; Beck, V; Barlow, S; Cowley, A; O'Hare, D (2004)
Reaction of 1,4-(BBr 2) 2C 6H 4 with cobaltocene gives a bimetallic cobalt complex with cyclopentadienyl and boratabenzene ligands. Oxidation allows the dicationic dicobalt(III) complex to be isolated; the bis(hexafluorophosphate) salt has been structurally characterized. Variable-temperature magnetic susceptibility measurements on the neutral dicobalt(II) complex showed substantial deviation from the Curie -Weiss law; a fit to the Bleaney-Bowers equation for a singlet ground state and a triplet excited state gave an exchange interaction of J = ca. -28 cm -1. Electrochemical studies, as well as near-infrared data on the mixed-valence species, suggest that the interaction between the metal centers is weak.